Germination Performance of Wild Lupine Seeds (Lupinus varius L.) in Jordan Using Different Breaking Dormancy Treatments - Obeidat , Wisam M.; AL SANE, Khaldoun O.; AL-EDWAN, Ahmad S.; AL-GHZAWI, Abdul Latief; ABULAILA, Khaled M.; AL-SALEM, Mohammad; JUHMANI, Abdul-salam; ALTAWAHA, Abdel Razzaq (Jordan Journal of Agricultural Sciences, 2025)
Wild lupine (Lupinus varius L.) is an annual plant native to the Mediterranean region. Only a few studies have investigated the germination performance of wild lupine seeds in the Mediterranean region and examined different effects of temperatures and multiple dormancy-breaking treatments, which could help crop breeders to develop varieties more resilient to climate change. This study was conducted to assess how different dormancy-breaking treatments, including hot water (80 °C), chemical scarification using sulfuric acid (H₂SO₄), and mechanical scarification, affect the germination rate and radicle length of wild lupine seeds when exposed to four controlled temperatures: 10, 14, 18, and 22 °C. A complete randomized design with three replications was used in this study. Mechanical scarification combined with a temperature of 22°C for 15 days was the most effective treatment for breaking the dormancy and resulted in the highest germination percentage (93.3%) and the highest radicle length (7.6 mm) for lupine seeds. In contrast, the lowest germination percentage (13.1-13.3%) was observed for H₂SO₄ and control wild lupine seeds (untreated) incubated at 10°C. In conclusion, mechanical scarification is an excellent method for breaking the seed dormancy of wild lupine seeds.